Drivers of biosonar click rates in bottlenose dolphins (Tursiops truncatus) over the West Florida Shelf - Baldachini, Marzia; Papale, Elena; Shearer, Jeanne M.; Wells, Randall S.; Jensen, Frants H. (Frontiers in Marine Science, 2025)
Understanding cetacean echolocation behavior is important for effective population monitoring and conservation. Using passive acoustic monitoring (PAM), researchers can listen for the biosonar clicks produced by echolocating animals to estimate both diurnal and seasonal variations in their presence and activity. Furthermore, if species-specific click rates are known, cue counting techniques can be used to provide an estimate of population density. This study investigated the click rates of wild bottlenose dolphins tagged with sound and movement recording DTAG3s during health assessments over the West Florida Shelf in the Gulf of Mexico to quantify individual variability and explore factors influencing click production. We observed modest but significant differences in click rates across individuals, and higher click rates during dives compared to inter-dive surface intervals. Within dives, dive depth was the most important in shaping click rates, reflecting that dolphins adjust their echolocation behavior to tailor their acoustic field of view based on both predator-prey distance and their proximity to other large reflectors such as the ocean bottom. Click rates also showed subtle diurnal peaks at dawn and dusk, aligning with increased foraging efforts. The findings lay the groundwork for bottlenose dolphin density estimation using the cue counting technique and underscore the importance of incorporating region-specific information on foraging ecology and diving behavior into models of click rates. Our study provides the first estimate of bottlenose dolphin click rates but calls for further research to refine these click rate estimates to facilitate acoustic monitoring of delphinids.